Noun-epithets of Dongba and Daba oral traditions - Xu, Duoduo (2022)
Dongba and Daba chants represent two of the few oral traditions still surviving in the world. In both traditions, the main category of formulaic expressions consists of traditional noun-epithets describing spirits. Dongba and Daba spirits can be classified into five categories, of which the noun-epithets used to describe them share similar features. Another significant percentage of noun-epithets portray figures of animals. Dongba and Daba chants are both chanted in odd-numbered metric patterns in which noun-epithets are adapted to the metric context. Besides the core expression (often a tetra-syllabic compound), several monosyllabic words not affecting the core meaning may be inserted as optional morphemes to modify the number of syllables in the noun-epithet. This study provides a systematic philological analysis of the vast repertoire of Daba and Dongba noun-epithets. Comparative mythology and comparative linguistics combine to present a comprehensive description of the stylistic features of Daba and Dongba noun-epithets.